1988
DOI: 10.1002/1097-4679(198811)44:6<891::aid-jclp2270440608>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Anglo- and Mexican-American performance on the MMPI administered in Spanish or English

Abstract: The MMPI was administered in either Spanish or English to 450 Anglo or Mexican‐Americans matched for sex and age. All 150 Anglo‐Americans were tested in English, while half the 300 Mexican‐Americans were tested in Spanish and the other half in English. A multivariate analysis of variance revealed significant age, sex, and language/ethnicity differences. Univariate analyses of variance demonstrated that Mexican‐Americans tested in Spanish scored significantly higher than either Anglos or Mexican‐Americans teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…There was a trend for underreporting measures to be elevated when participants responded honestly to the PAI in Spanish. These findings are similar to those observed for underreporting and defensiveness measures on the Minnesota Multiphasic Person- ality Inventory-2 (Lucio, Reyes-Lagunes, & Scott, 1994;Whitworth, 1988), and they suggest that practitioners need to be aware of this potential difference when interpreting any personality measure scores from Spanish-speaking clients in practice. Our findings should be interpreted cautiously as to their support for the Spanish-language validity scales.…”
Section: Discussionsupporting
confidence: 76%
“…There was a trend for underreporting measures to be elevated when participants responded honestly to the PAI in Spanish. These findings are similar to those observed for underreporting and defensiveness measures on the Minnesota Multiphasic Person- ality Inventory-2 (Lucio, Reyes-Lagunes, & Scott, 1994;Whitworth, 1988), and they suggest that practitioners need to be aware of this potential difference when interpreting any personality measure scores from Spanish-speaking clients in practice. Our findings should be interpreted cautiously as to their support for the Spanish-language validity scales.…”
Section: Discussionsupporting
confidence: 76%
“…Clearly, the role of acculturation in cross-cultural research appeared to have influenced the results of this investigation. Previous research studies have found a relationship between lower levels of acculturation and higher scores (more pathological ratings) on rating scales (Negy, Leal-Puente, Trainor, & Carlson, 1997, Negy & Woods, 1993; however, these differences can be reduced or eliminated if acculturation is controlled statistically (Montgomery, Arnold, & Orozco, 1990;Whitworth, 1988). Both studies utilizing rating scales (i.e., MMPI) revealed that the reported differences between Mexican Americans and Anglos were suppressed by statistically controlling acculturation.…”
Section: Acculturation Effectsmentioning
confidence: 98%
“…Eighty-five percent of these studies involved the MMPI and none examined the validity and reliability of commonly used diagnostic tools. Researchers have found both acculturation and language differences in response to the MMPI (Whitworth, 1988;Montgomery & Orozco, 1983;Padilla, Olmedo, & Loya, 1982). Yet shorter assessment tools such as the BDI are more commonly used in treatment outcome research, and in community mental-health settings, as measures of distress or symptom severity.…”
Section: Introductionmentioning
confidence: 99%